answer:
x^2 - 3x - 18
explanation:
(x+3)(x-6)
you need to do distributive property and it will give you that answer
What is that i can't see it
Answer: x=−3
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
5(x−4)+3x−9x=6−(2x+5)+8x
(5)(x)+(5)(−4)+3x+−9x=6+−2x+−5+8x(Distribute)
5x+−20+3x+−9x=6+−2x+−5+8x
(5x+3x+−9x)+(−20)=(−2x+8x)+(6+−5)(Combine Like Terms)
−x+−20=6x+1
−x−20=6x+1
Step 2: Subtract 6x from both sides.
−x−20−6x=6x+1−6x
−7x−20=1
Step 3: Add 20 to both sides.
−7x−20+20=1+20
−7x=21
Step 4: Divide both sides by -7.
−7x over -7
=
21 over -7
x=−3